2013
DOI: 10.1007/s11135-013-9928-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of mixed methods designs in substance research: a methodological necessity in Nigeria

Abstract: The utility of mixed methods (qualitative and quantitative) is becoming increasingly accepted in health sciences, but substance studies are yet to substantially benefit from such utilities. While there is a growing number of mixed methods alcohol articles concerning developed countries, developing nations are yet to embrace this method. In the Nigerian context, the importance of mixed methods research is yet to be acknowledged. This article therefore, draws on alcohol studies to argue that mixed methods design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Additionally, the data were collected from a university campus and as such, the views expressed here may not represent that of young people from the region or from Nigeria more broadly. However, this study makes important contributions to gender and alcohol research by studying an understudied group using qualitative research methods, which are underutilised among alcohol scholars in Nigeria [71]. The study also provides direction for further research.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the data were collected from a university campus and as such, the views expressed here may not represent that of young people from the region or from Nigeria more broadly. However, this study makes important contributions to gender and alcohol research by studying an understudied group using qualitative research methods, which are underutilised among alcohol scholars in Nigeria [71]. The study also provides direction for further research.…”
Section: Resultsmentioning
confidence: 99%
“…Another shortcoming is that the data were elicited from one university campus; thus, the views expressed by the participants may not necessarily represent the opinions of other Nigerian students. Despite these limitations, the study has, for the first time in Nigeria, employed a qualitative methodology that is underutilised by Nigerian substance researchers [ 62 ] to study an understudied group. In doing this, it extends the existing literature on the motivations to use alcohol for sexual purposes and the associated risks.…”
Section: Discussionmentioning
confidence: 99%
“…Funding allocations from federal agencies that support scientific research can signal recognition of a particular methodology within the scientific community, as well as proficiency of investigators in using such methods to move a field of inquiry forward. Internationally, there is a small but growing collection of literature describing the status and prevalence of funding for mixed methods research (e.g., Dumbili, 2014; Dupin, Debout, & Rothan-Tondeur, 2014; Islam & Oremus, 2014; O’Cathain et al, 2007; Zhou & Creswell, 2012). In the United States, an analysis of trends in health-related mixed methods proposals funded by federal agencies between 1997 and 2008 indicated that the number of mixed methods studies was increasing, although the proportion of mixed methods studies as a percentage of all federal grants remained low (Plano Clark, 2010).…”
mentioning
confidence: 99%